A method for selectively catalyzing and oxidizing 5-hydroxymethylfurfural to produce 2,5-furandicarboxylic acid using nanostructured multi-metal oxide

By using subcritical technology to prepare nanostructured polymetal oxide catalysts during biomass conversion, the problems of low conversion efficiency and poor selectivity in the prior art are solved, and the effect of efficient catalytic conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid is achieved, providing a low-cost catalytic solution for industrialization.

CN119455977BActive Publication Date: 2025-04-08ZHEJIANG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510060930.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The prior art has problems such as low conversion efficiency, poor selectivity, and harsh conditions in the process of conversion of biomass to high-value compounds, making it difficult to develop efficient, stable and low-cost catalysts.

Method used

By adjusting temperature and pressure, subcritical technology is used to prepare nano-microstructured polymetal oxide catalysts, regulate their micromorphology and size, stimulate the active sites of polymetal oxides, and improve catalytic performance.

Benefits of technology

The efficient catalytic conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid of polymetal oxides has been achieved, which significantly improves yields and provides a new method for non-precious metal catalysts for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455977B_ABST
    Figure CN119455977B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for selectively catalyzing and oxidizing 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid using a nanostructured multi-metal oxide. The present invention mixes different metal salts with alkaline additives in a solvent, utilizes the characteristics of excellent solubility and diffusion performance of the solvent in a subcritical state, makes the metal ions fully contact and rapidly crystallize in the subcritical fluid, regulates the temperature and pressure in the reaction process to achieve the regulation of the microstructure of the multi-metal oxide, thereby stimulating the multi-metal active sites, and then roasts to prepare a multi-metal oxide catalyst, which can realize the efficient and highly selective conversion of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid under alkaline and aqueous solution conditions. The catalyst prepared by this method has the advantages of high dispersibility, strong controllability, and rapid crystallization. Compared with precious metal catalysts, the multi-metal oxide catalyst prepared by the method of the present invention has low cost, high stability, can be recycled, and has a wide application environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomass resource utilization and multi-metal oxide preparation, and specifically relates to a method for using nano-microstructured multi-metal oxides for selective catalytic oxidation of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid. Background Art

[0002] Biomass is a renewable organic resource with abundant reserves, wide distribution and easy access. It has the advantages of being renewable and biodegradable, and is an ideal energy substitute. 5-Hydroxymethylfurfural, as an important bio-based platform compound, has received widespread attention due to its unique chemical structure and versatility. 5-Hydroxymethylfurfural can be converted into 2,5-furandicarboxylic acid through a series of catalytic reactions. The latter is a key high-value precursor that can be used to synthesize a variety of fine chemicals. The most noteworthy thing is that 2,5-furandicarboxylic acid has a conjugated rigid ring and dicarboxylic acid structure similar to terephthalic acid. It is an excellent precursor for synthetic polymers and can be used as an alternative material to terephthalic acid. With its renewability and easy degradation, it can alleviate the plastic pollution situation. However, the conversion of biomass to high-value compounds generally has problems such as low conversion efficiency, poor selectivity, and harsh conditions. Therefore, the development of efficient, stable and low-cost catalysts has become an important issue that needs to be solved urgently.

[0003] Subcritical fluids have unique advantages in the field of nanomaterial preparation due to their excellent solubility and mass transfer properties. The preparation of catalysts using subcritical technology has the advantages of high dispersibility, strong controllability, and rapid crystallization. Metal ions can quickly form smaller nanoparticles in subcritical fluids. By changing some conditions in the subcritical preparation of catalysts, the microscopic morphology and size of multi-metal oxides can be precisely controlled, thereby stimulating the active sites of multi-metal oxides and affecting the activity of the catalyst.

[0004] At present, precious metal materials have shown excellent catalytic performance in the process of catalyzing the conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid, but due to their high cost and difficulty in recycling, researchers prefer to find low-cost transition metal catalysts to replace precious metals. Studies have shown that multi-metal oxides have heterogeneous catalytic effects in electrocatalysis, photocatalysis and thermal catalysis. Multi-metal oxides are usually composed of two or more metal oxides. Due to the synergistic effect of multiple metals, they have rich active sites and show properties superior to single metal oxides. Therefore, designing a controllable and efficient catalyst preparation method to activate multi-metal active sites and synthesize highly active catalysts to efficiently catalyze the conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid has become a major challenge at present. Summary of the invention

[0005] In view of the above situation, the purpose of the present invention is to provide a method for selectively catalyzing the oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid using a nanostructured multi-metal oxide. The nanostructure of the multi-metal oxide is regulated by adjusting the temperature and pressure during the reaction. The obtained multi-metal oxide has the characteristics of small size, multiple active sites and high catalytic activity, which provides a new method for developing a non-precious metal catalyst to catalyze the oxidation conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid.

[0006] The technical solution adopted in the present invention is as follows:

[0007] A subcritical preparation method for a multi-metal oxide with adjustable nano-microstructure comprises the following steps:

[0008] Step 1: dissolving a metal salt in an aqueous solvent, uniformly dispersing the mixture by ultrasonication, dripping an alkaline additive solution into the mixture under stirring, and fully stirring and mixing the mixture to obtain a uniform mixed solution; wherein the metal salt is a chloride, nitrate, acetate or sulfate corresponding to two or more metal elements selected from magnesium, aluminum, iron, cobalt, manganese, nickel, copper, zinc, gallium and indium;

[0009] Step 2: The mixed solution obtained in step 1 is transferred into a temperature- and pressure-controlled reactor, and the temperature and pressure of the reactor are adjusted to make the liquid in the reactor reach a subcritical state, and react to rapidly form nanoparticles;

[0010] Step 3: centrifugally separating the mixed suspension prepared in step 2, and sequentially washing, drying, and grinding to obtain a multi-metal oxide precursor;

[0011] Step 4: placing the multi-metal oxide precursor prepared in step 3 in a muffle furnace for calcination to obtain the multi-metal oxide;

[0012] The reaction temperature of step 2 is 150-200°C, and the reaction pressure is 0.4-5 MPa.

[0013] Furthermore, the metal salt in step 1 is a salt of two metals, the first metal is Mn, the second metal is Co, Cu or Ni, and the molar ratio of the first metal to the second metal is 1.5-3:1, preferably 2-2.5:1.

[0014] Furthermore, the metal salt in step 1 is a salt of two metals, the first metal is Co, the second metal is Cu or Cu and Zn, the molar ratio of the first metal to the second metal is 1.5-3:1, preferably 2-2.5:1; when the second metal is Cu and Zn, the molar ratio of the two is 1.5-3:1, preferably 2-2.5:1.

[0015] Furthermore, in step 1, the alkaline additive is at least one of sodium hydroxide, potassium hydroxide, aqueous ammonia, sodium carbonate, and potassium carbonate, and the alkaline additive solution is dripped into the metal salt solution to adjust the pH to 9-12.

[0016] Furthermore, in step 2, the reaction temperature is 170-180°C, and pressurized nitrogen is introduced into the reactor to make the reaction pressure in the reactor higher than the autogenous pressure of water in the reactor, and the reaction pressure is adjusted to 1.5-2 MPa.

[0017] Furthermore, the calcination temperature in step 4 is 300-400°C.

[0018] The present invention provides a multi-metal oxide with adjustable nano-microstructure, which can be well used in catalyzing the reaction of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid. The application method is as follows: adding the multi-metal oxide, an alkaline additive and a 5-hydroxymethylfurfural solution into a microreactor with controllable temperature and pressure, sealing the microreactor, and catalyzing the oxidation of 5-hydroxymethylfurfural to generate 2,5-furandicarboxylic acid under the conditions of a temperature of 100-150°C, an oxygen pressure of 0.5-4 MPa and continuous magnetic stirring; after the reaction is completed, centrifuging and recovering the multi-metal oxide material.

[0019] Furthermore, the concentration of the 5-hydroxymethylfurfural solution is 10-100 mM, the mass ratio of the multi-metal oxide to 5-hydroxymethylfurfural is 1.2-2:1; the alkaline additive is sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or calcium hydroxide, and the molar ratio of the alkaline additive to 5-hydroxymethylfurfural is 1 ~ 4:1.

[0020] The beneficial effects achieved by the present invention are:

[0021] 1) The present invention utilizes the characteristics of high diffusion coefficient, high reaction rate and low surface tension of the solvent in the subcritical state, and achieves effective regulation of the nanostructure of the multi-metal oxide by adjusting the temperature and pressure during the reaction process, so that the formed multi-metal oxide has abundant active sites.

[0022] 2) The multi-metal oxide material prepared by the present invention can be used for the oxidation reaction of 5-hydroxymethylfurfural. By exerting its multi-metal synergistic effect, the multi-metal active sites are stimulated, the interfacial reaction between 5-hydroxymethylfurfural and the catalyst material is significantly promoted, and the yield of 2,5-furandicarboxylic acid production is improved.

[0023] 3) The present invention can provide a new method for replacing precious metal catalysts and developing new non-precious metal functional materials for the 2,5-furandicarboxylic acid industry. The multi-metal oxide material prepared by the present invention can be used in the oxidation reaction of 5-hydroxymethylfurfural, play a catalytic role, and improve the product conversion rate. The non-precious metal Mn, Co, and Cu-based multi-metal oxide materials have excellent catalytic effects, providing a new possibility for the industrial production of 2,5-furandicarboxylic acid using non-precious metal catalysts. In addition, in order to reduce the cost of precious metal use, reduce environmental pollution, and develop non-precious metal catalysts to promote the long-term development of the 5-hydroxymethylfurfural oxidation industry, a new method is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD pattern of the CoMn2O4 sample prepared in Example 1 of the present invention.

[0025] Figure 2 This is a SEM image of the CoMn2O4 sample prepared in Example 1 of the present invention.

[0026] Figure 3 This is the TEM image of the CoMn2O4 sample prepared in Example 1 of the present invention.

[0027] Figure 4 It is a schematic structural diagram of the subcritical hydrothermal reaction device of the present invention. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0029] The mass concentration of ammonia water in the embodiment of the present invention is 25-28%.

[0030] The structural schematic diagram of the subcritical hydrothermal reaction device used in the embodiment of the present invention is as follows Figure 4 As shown, it includes a reactor 5 and a constant temperature heating jacket 6 arranged outside the reactor 5 for heating the reactor 5. A stirring magnet is added inside the reactor 5, and the reactor 5 is placed on a magnetic stirrer. An air inlet 7 and an air outlet 8 are arranged on the top of the reactor 5. The air inlet 7 is connected to the nitrogen bottle 1 through a pipeline via an air inlet valve 4, a flow meter 3, and a gas delivery pump 2. The air outlet 8 is connected to an exhaust pipe with an exhaust valve 13. A temperature measuring port 9 is also arranged on the top of the reactor 5. A temperature measuring probe 11 extends into the reactor 5 through the temperature measuring port 9 to detect the liquid temperature inside the reactor 5. A pressure detection port 10 is arranged on the top of the reactor 5, and the pressure detection port is connected to a pressure sensor 12.

[0031] Example 1 The CoMn2O4 catalyst is prepared by controlling the temperature and pressure using subcritical technology, and the steps are as follows:

[0032] 1) Dissolve 1.5 mmol Co(NO3)2·6H2O in 30 mL ultrapure water and disperse it evenly by ultrasonic. Then weigh 3 mmol Mn(NO3)2·4H2O and dissolve it in 30 mL ultrapure water and disperse it evenly by ultrasonic. Mix the two solutions and continue magnetic stirring. Add ammonia water dropwise into the mixture, adjust the pH to 11, and stir to mix evenly.

[0033] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, nitrogen is introduced to remove air and oxygen in the system, and magnetic stirring is maintained. While heating the reactor, pressurized N2 is introduced into the reactor, the temperature in the reactor is precisely controlled to be 180°C and the gas pressure in the reactor is 1.5 MPa, the reaction is continued for 180 min and then centrifuged. The solid obtained by centrifugation is washed 3 times with water and anhydrous ethanol respectively, the washed material is placed in a vacuum drying oven, vacuum dried at 80°C for 12 h, and the dried solid is calcined at 350°C in a muffle furnace to obtain the CoMn2O4 catalyst.

[0034] The characterization results of the XRD, SEM and TEM images of the CoMn2O4 catalyst prepared in Example 1 are shown in Figure 1 , Figure 2 and Figure 3 The XRD results show that CoMn2O4 was successfully prepared, and the SEM and TEM images show that the CoMn2O4 prepared by the method of the present invention has a granular nanostructure and abundant active sites.

[0035] Example 2 Preparation of CuMn2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0036] Example 2 Preparation method of CuMn2O4 catalyst Repeat Example 1, the only difference is that "Co(NO3)2·6H2O is replaced by an equal molar amount of Cu(NO3)2·2.5H2O", and the other conditions remain unchanged, and finally the CuMn2O4 catalyst is obtained.

[0037] Example 3 Preparation of NiMn2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0038] Example 3 Preparation method of NiMn2O4 catalyst Repeat Example 1, the only difference is that "Co(NO3)2·6H2O is replaced by an equal molar amount of Ni(NO3)2·6H2O", and the other conditions remain unchanged, and finally the NiMn2O4 catalyst is obtained.

[0039] Example 4 Preparation of MgMn2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0040] Example 4 Preparation method of MgMn2O4 catalyst Repeat Example 1, the only difference is that "Co(NO3)2·6H2O is replaced by an equal molar amount of Mg(NO3)2·6H2O", and the other conditions remain unchanged, and finally the MgMn2O4 catalyst is obtained.

[0041] Example 5 Preparation of FeMn2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0042] Example 5 Preparation method of FeMn2O4 catalyst Repeat Example 1, the only difference is that "Co(NO3)2·6H2O is replaced by an equal molar amount of Fe(NO3)2·9H2O", and the other conditions remain unchanged, and finally the FeMn2O4 catalyst is obtained.

[0043] Example 6 Preparation of ZnMn2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0044] Example 6 Preparation method of ZnMn2O4 catalyst: Example 1 is repeated, the only difference is that "Co(NO3)2·6H2O is replaced by an equal molar amount of Zn(NO3)2·6H2O", and the other conditions remain unchanged, and finally the ZnMn2O4 catalyst is obtained.

[0045] Example 7 Preparation of MnAl2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0046] 1) Dissolve 1.5 mmol Mn(NO3)2·4H2O in 30 mL ultrapure water and disperse it evenly by ultrasonic. Then weigh 3 mmol Al(NO3)2·9H2O and dissolve it in 30 mL ultrapure water and disperse it evenly by ultrasonic. Mix the two solutions with continuous magnetic stirring. Add ammonia water dropwise into the mixture, adjust the pH to 11, and stir to mix evenly.

[0047] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, nitrogen is introduced to remove air and oxygen in the system, and magnetic stirring is maintained. While heating the reactor, pressurized N2 is introduced into the reactor, the temperature in the reactor is precisely controlled to be 180°C and the gas pressure in the reactor is 1.5 MPa, the reaction is continued for 180 min and then centrifuged, the solid obtained by centrifugation is washed 3 times with water and anhydrous ethanol respectively, the washed material is placed in a vacuum drying oven, vacuum dried at 80°C for 12 h, and the dried solid is calcined at 350°C in a muffle furnace to obtain the MnAl2O4 catalyst.

[0048] Example 8 Preparation of MnGa2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0049] Example 8 The preparation steps of MnGa2O4 catalyst are repeated in Example 7, with the only difference being that "Al(NO3)2·9H2O is replaced by an equal molar amount of Ga(NO3)2·9H2O" and the other conditions remain unchanged, and finally the MnGa2O4 catalyst is obtained.

[0050] Example 9 Preparation of MnIn2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0051] Example 9 The preparation steps of MnIn2O4 catalyst were repeated in Example 8, with the only difference being that "Ga(NO3)2·9H2O was replaced by an equal molar amount of In(NO3)2·6H2O" and the other conditions remained unchanged, and finally the MnIn2O4 catalyst was obtained.

[0052] Example 10 Preparation of FeCo2O4 catalyst by subcritical technology temperature and pressure control and application, the steps are as follows:

[0053] 1) Dissolve 1.5 mmol Fe(NO3)2·9H2O in 30 mL ultrapure water and disperse it evenly by ultrasonic. Then weigh 3 mmol Co(NO3)2·6H2O and dissolve it in 30 mL ultrapure water and disperse it evenly by ultrasonic. Mix the two solutions with continuous magnetic stirring. Add ammonia water dropwise into the mixture, adjust the pH to 11, and stir to mix evenly.

[0054] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, nitrogen is introduced to remove air and oxygen in the system, and magnetic stirring is maintained. While heating the reactor, pressurized N2 is introduced into the reactor, the temperature in the reactor is precisely controlled to be 180°C and the gas pressure in the reactor is 1.5 MPa, the reaction is continued for 180 min and then centrifuged, the solid obtained by centrifugation is washed 3 times with water and anhydrous ethanol respectively, the washed material is placed in a vacuum drying oven, vacuum dried at 80°C for 12 h, and the dried solid is calcined at 350°C in a muffle furnace to obtain the FeCo2O4 catalyst.

[0055] Example 11 Preparation of ZnCo2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0056] Example 11 Preparation steps of ZnCo2O4 catalyst The steps of Example 10 were repeated, with the only difference being that "Fe(NO3)2·9H2O was replaced by an equal molar amount of Zn(NO3)2·6H2O" and the other conditions remained unchanged, and finally the ZnCo2O4 catalyst was obtained.

[0057] Example 12 Preparation of CuCo2O4 Catalyst by Subcritical Technology Temperature and Pressure Control

[0058] Example 12 Preparation steps of CuCo2O4 catalyst The steps of Example 10 were repeated, with the only difference being that "Fe(NO3)2·9H2O was replaced by an equal molar amount of Cu(NO3)2·2.5H2O" and the other conditions remained unchanged, and finally the CuCo2O4 catalyst was obtained.

[0059] Example 13 Preparation of Cu by subcritical temperature and pressure control 0.7 Zn 0.3 Co2O4 catalyst and application, the steps are as follows:

[0060] 1) Dissolve 1.05 mmol Cu (NO3)2·2.5H2O and 0.45 mmol Zn (NO3)2·6H2O in 30 mL ultrapure water and disperse them evenly by ultrasonic. Then weigh 3 mmol Co(NO3)2·6H2O and dissolve it in 30 mL ultrapure water and disperse it evenly by ultrasonic. Mix the two solutions with continuous magnetic stirring. Add ammonia water dropwise into the mixture, adjust the pH to 11, and stir to mix evenly.

[0061] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, nitrogen is introduced to remove air and oxygen in the system, and magnetic stirring is maintained. While heating the reactor, pressurized N2 is introduced into the reactor, and the temperature in the reactor is precisely controlled to be 180°C and the gas pressure in the reactor is 1.5 MPa. The reaction is continued for 180 min and then centrifuged. The solid obtained by centrifugation is washed 3 times with water and anhydrous ethanol respectively. The washed material is placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried solid is calcined at 350°C in a muffle furnace to obtain the Cu 0.7 Zn 0.3 Co2O4 catalyst.

[0062] The catalysts prepared in Examples 1-13 were characterized by SEM, showing that the catalysts prepared by the method of the present invention all had a granular nanostructure.

[0063] Example 14 Preparation of CoMn2O4 catalyst by subcritical temperature control technology:

[0064] 1) Dissolve 1.5 mmol Co(NO3)2·6H2O in 30 mL ultrapure water and disperse it evenly by ultrasonic. Then weigh 3 mmol Mn(NO3)2·4H2O and dissolve it in 30 mL ultrapure water and disperse it evenly by ultrasonic. Mix the two solutions and continue magnetic stirring. Add ammonia water to the mixture, adjust the pH to 11, and stir to mix evenly.

[0065] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, nitrogen is introduced to remove air and oxygen in the system, and magnetic stirring is maintained. The reactor is heated, and the introduction of pressurized N2 into the reactor is stopped. The temperature in the reactor is controlled to be 200°C by a heating device. When the temperature of the reactor reaches 200°C, the autogenous pressure in the reactor reaches 1.5 MPa. The reaction is continued for 180 min and then centrifuged. The solid obtained by centrifugation is washed 3 times with water and anhydrous ethanol respectively. The washed material is placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried solid is calcined at 350°C in a muffle furnace to obtain the CoMn2O4 catalyst.

[0066] Example 15 Preparation of CoMn2O4 catalyst by subcritical technology temperature and pressure control and application, the steps are as follows:

[0067] 1.5 mmol Co(NO3)2·6H2O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonic. Then 3 mmol Mn(NO3)2·4H2O was weighed and dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonic. The two solutions were mixed and continuously magnetically stirred. Ammonia water was dropped into the mixed solution to adjust the pH to 11. After stirring and mixing evenly, the mixture was transferred into a reactor. The reactor was sealed and nitrogen was introduced to remove the air and oxygen in the system while magnetic stirring was maintained. While heating the reactor, pressurized N2 was introduced into the reactor. The temperature in the reactor was precisely controlled to be 150°C and the gas pressure in the reactor was 1.5 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed with water and anhydrous ethanol three times respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried solid was calcined at 350°C in a muffle furnace to obtain the CoMn2O4 catalyst.

[0068] Application Example 1 The catalyst is used for the oxidation reaction of 5-hydroxymethylfurfural, and the specific process is as follows:

[0069] A microreactor device was used, the inner tank was 25 mL, and the heating jacket was used to heat and control the temperature. 50 mg of catalyst, 0.042 g of sodium bicarbonate, and 5 mL of 50 mM 5-hydroxymethylfurfural aqueous solution were added to the inner tank of the microreactor device. The microreactor device was sealed, magnetic stirring was continued at 600 rpm, oxygen was pressurized to 1.5 MPa, the reaction temperature was set to 130 ° C, and the temperature was raised from room temperature at a heating rate of 2 ° C / min. After the temperature reached 130 ° C, the reaction time at 130 ° C was started, and the reaction liquid with a reaction time of 8 hours was taken for analysis and detection, and the conversion rate and yield of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid were calculated.

[0070] According to the above experimental process, when the catalysts prepared in Examples 1-15 are used respectively, the conversion rates and yields of 5-hydroxymethylfurfural converted to 2,5-furandicarboxylic acid by the catalysts of different Examples are shown in Table 1.

[0071] Table 1

[0072] .

[0073] From Table 1 we can see that:

[0074] 1) The composition of the catalyst has a great influence on the catalytic activity of the 5-hydroxymethylfurfural oxidation reaction. The non-precious metal Mn, Co, and Cu-based multi-metal oxide materials have excellent catalytic effects. In addition, a small amount of Zn added to the CuCo2O4 catalyst also achieves good catalytic reaction effects.

[0075] 2) Comparing the catalytic reaction results of Example 1 with those of Examples 14 and 15, it can be seen that when the gas pressure in the reactor during catalyst preparation is also 1.5 MPa, different reaction temperatures have a relatively large impact on the catalyst activity.

[0076] In order to test the performance of the prepared catalyst, the CoMn2O4 catalyst prepared in Example 1 was repeatedly applied in the 5-hydroxymethylfurfural oxidation reaction. After each batch of reaction was completed for 8 hours, the catalyst was centrifuged and then washed with deionized water before being put into the next batch of 5-hydroxymethylfurfural oxidation reaction. According to the above experimental process, after the CoMn2O4 catalyst prepared in Example 1 underwent five 5-hydroxymethylfurfural oxidation cycle experiments, the yield of FDCA fluctuated only slightly, with a fluctuation range of about 1.5%. This shows that the catalyst prepared by the present invention has excellent stability, can be repeatedly used, and has industrial prospects.

[0077] Comparative Example 1: Preparation and application of Mn3O4 catalyst by conventional hydrothermal method, the steps are as follows:

[0078] 2.25 mmol Mn(NO3)2·4H2O was dissolved in 30 mL ultrapure water, and the mixture was uniformly dispersed by ultrasonication, and magnetic stirring was continued. Ammonia water was added dropwise to adjust the pH to 11. After stirring and mixing, the mixture was transferred into a 50 mL polytetrafluoroethylene liner of a reactor. The stainless steel reactor was sealed, and the reaction was continued at 180°C for 8 h, followed by centrifugal separation. The solid was washed 3 times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80°C for 12 h to obtain the Mn3O4 catalyst.

[0079] The SEM image of the Mn3O4 catalyst prepared in Comparative Example 1 shows that the prepared Mn3O4 has a nanosphere cluster structure.

[0080] The catalytic method of Example 1 was used to prepare the Mn3O4 sample in Comparative Example 1 for the oxidation reaction of 5-hydroxymethylfurfural. Under the conditions of a reaction temperature of 130°C and a reaction time of 8 h, the 5-hydroxymethylfurfural conversion rate after the oxidation reaction of 5-hydroxymethylfurfural reached stability could reach 100%, and the yield of 2,5-furandicarboxylic acid could reach up to 26.7%.

[0081] Comparative Example 2 Preparation of Co3O4 catalyst and application by conventional hydrothermal method, the steps are as follows:

[0082] 2.25 mmol Co(NO3)2·6H2O was dissolved in 30 mL ultrapure water, and the mixture was uniformly dispersed by ultrasonication, and magnetic stirring was continued. Ammonia water was added dropwise to adjust the pH to 11. After stirring and mixing, the mixture was transferred into a 50 mL polytetrafluoroethylene liner of a reactor. The stainless steel reactor was sealed, and the reaction was continued at 180°C for 8 h, followed by centrifugal separation. The solid was washed three times with water and anhydrous ethanol, respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80°C for 12 h to obtain the Co3O4 catalyst.

[0083] The SEM image of the Co3O4 catalyst prepared in Comparative Example 2 shows that the prepared Co3O4 has a nanosphere cluster structure.

[0084] The Co3O4 sample prepared in Comparative Example 2 was used for the oxidation reaction of 5-hydroxymethylfurfural by using the catalytic method of Application Example 1. Under the conditions of reaction temperature of 130°C and reaction time of 8 h, the conversion rate of 5-hydroxymethylfurfural after the oxidation reaction of 5-hydroxymethylfurfural reached stability was 89.7%, and the conversion rate of 2,5-furandicarboxylic acid was as high as 18.9%.

[0085] Comparative Example 3 Preparation of Fe3O4 catalyst and application by conventional hydrothermal method, the steps are as follows:

[0086] 2.25 mmol Fe(NO3)2·9H2O was dissolved in 30 mL ultrapure water, and the mixture was uniformly dispersed by ultrasonication, and magnetic stirring was continued. Ammonia water was added dropwise to adjust the pH to 11. After stirring and mixing evenly, the mixture was transferred into a 50 mL polytetrafluoroethylene liner of a reactor. The stainless steel reactor was sealed, and the reaction was continued at 180°C for 8 h, followed by centrifugal separation. The solid was washed three times with water and anhydrous ethanol, respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80°C for 12 h to obtain the Fe3O4 catalyst.

[0087] The Fe3O4 sample prepared in Comparative Example 3 was used for the oxidation reaction of 5-hydroxymethylfurfural by using the catalytic method of Application Example 1. Under the conditions of reaction temperature of 130°C and reaction time of 8 h, the conversion rate of 5-hydroxymethylfurfural after the oxidation reaction of 5-hydroxymethylfurfural reached stability was 76.9%, and the yield of 2,5-furandicarboxylic acid was as high as 11.7%.

[0088] Comparative Example 4 Preparation of CoMn2O4 catalyst by subcritical technology temperature control and application, the steps are as follows:

[0089] 1.5 mmol Co(NO3)2·6H2O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonic. Then 3 mmol Mn(NO3)2·4H2O was weighed and dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonic. The two solutions were mixed and continuously magnetically stirred. Ammonia water was dropped into the mixed solution to adjust the pH to 11. After stirring and mixing evenly, the mixture was transferred into the reactor. The reactor was sealed and magnetic stirring was maintained. The temperature in the reactor was controlled to be 150 ℃ by a heating device. When the temperature of the reactor reached 150 ℃, the autogenous pressure of the water in the reactor was 0.4 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed 3 times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80 ℃ for 12 h. The dried solid was calcined at 350 ℃ in a muffle furnace to obtain the CoMn2O4 catalyst.

[0090] The CoMn2O4 sample prepared in Comparative Example 4 was used for the 5-hydroxymethylfurfural oxidation reaction, and its basic steps were the same as those of the catalyst used in Examples 1-15 for the 5-hydroxymethylfurfural oxidation reaction, except that the catalyst was CoMn2O4 prepared in Comparative Example 4. Under the conditions of a reaction temperature of 130°C and a reaction time of 8 h, the 5-hydroxymethylfurfural conversion rate after the 5-hydroxymethylfurfural oxidation reaction reached stability could reach 100%, and the yield of 2,5-furandicarboxylic acid could reach up to 68.7%.

[0091] Comparative Example 5 Preparation of CoMn2O4 catalyst by subcritical technology temperature control and application, the steps are as follows:

[0092] 1.5 mmol Co(NO3)2·6H2O was dissolved in 30 mL ultrapure water and dispersed uniformly by ultrasonication. Then 3 mmol Mn(NO3)2·4H2O was weighed and dissolved in 30 mL ultrapure water and dispersed uniformly by ultrasonication. The two solutions were mixed and continuously magnetically stirred. Ammonia water was dropped into the mixed solution, pH was adjusted to 11, and after stirring and mixing uniformly, it was transferred into the reactor. The reactor was sealed and magnetic stirring was maintained. The temperature in the reactor was controlled to 180 ℃ by a heating device. When the temperature of the reactor reached 180 ℃, the autogenous pressure of the water in the reactor was 0.93 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed 3 times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80 ℃ for 12 h. The dried solid was calcined at 350 ℃ in a muffle furnace to obtain the CoMn2O4 catalyst.

[0093] The CoMn2O4 sample prepared in Comparative Example 5 was used for the 5-hydroxymethylfurfural oxidation reaction, and its basic steps were the same as those of the catalyst used in Examples 1-13 for the 5-hydroxymethylfurfural oxidation reaction, except that the catalyst was CoMn2O4 prepared in Comparative Example 5. Under the conditions of a reaction temperature of 130°C and a reaction time of 8 h, the 5-hydroxymethylfurfural conversion rate after the 5-hydroxymethylfurfural oxidation reaction reached stability could reach 100%, and the yield of 2,5-furandicarboxylic acid could reach up to 83.7%.

[0094] The conclusions of the comparison between the embodiments and the comparative examples are as follows:

[0095] 1) By comparing the experimental results of Comparative Examples 1-3 with Comparative Examples 4-5, it can be seen that in the reaction of HMF oxidation to FDCA, the multi-metal catalyst has abundant active sites due to the synergistic effect of multiple metals, and exhibits characteristics superior to those of a single metal oxide.

[0096] 2) From the comparison of Comparative Examples 4 and 5, it can be seen that in the reaction of HMF oxidation to FDCA, CoMn2O4 is prepared by autogenous pressure temperature control under subcritical state, and the CoMn2O4 prepared at 180 °C has better catalytic activity.

[0097] 3) From the comparison between Example 1 and Comparative Example 5, it can be seen that in the reaction of HMF oxidation to FDCA, the catalyst prepared by controlled pressure under subcritical state has better catalytic activity than the catalyst prepared by conventional autogenous pressure. This is attributed to the fact that under relatively high pressure environment, the changes in the reaction rate and pressure of the system lead to differences in the active sites of the surface structure of the nanomaterial, which directly affects the activity performance of the material.

[0098] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. A method for preparing nanostructured multi-metal oxides, characterized in that The following steps are involved: Step 1: dissolving a metal salt in an aqueous solvent, uniformly dispersing the mixture by ultrasonication, dripping an alkaline additive solution into the mixture under stirring, adjusting the pH value to 9-12, and fully stirring and mixing the mixture to obtain a uniform mixed solution; wherein the metal salt is a chloride, nitrate, acetate or sulfate corresponding to the two metal elements of cobalt and manganese; Step 2: The mixed solution obtained in step 1 is transferred into a temperature- and pressure-controlled reactor, and the temperature and pressure of the reactor are adjusted to make the liquid in the reactor reach a subcritical state, and react to rapidly form nanoparticles; Step 3: centrifugally separating the mixed suspension prepared in step 2, and sequentially washing, drying, and grinding to obtain a multi-metal oxide precursor; Step 4: placing the multi-metal oxide precursor prepared in step 3 in a muffle furnace for calcination to obtain a multi-metal oxide, wherein the multi-metal oxide is CoMn2O4; In step 2, the reaction temperature is 170-180° C. By introducing pressurized nitrogen into the reactor, the reaction pressure in the reactor is made higher than the autogenous pressure of water in the reactor, and the reaction pressure is adjusted to 1.5-2 MPa.

2. The method for preparing a nanostructured multi-metal oxide according to claim 1, characterized in that In step 1, the alkaline additive solution is an aqueous solution of at least one of sodium hydroxide, potassium hydroxide, aqueous ammonia, sodium carbonate and potassium carbonate.

3. The method for preparing a nanostructured multi-metal oxide according to claim 1, characterized in that The calcination temperature in step 4 is 300-400°C.

4. A nanostructured multi-metal oxide prepared by the method according to any one of claims 1 to 3.

5. Use of a nanostructured multi-metal oxide as claimed in claim 4 in catalyzing the oxidation reaction of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid.

6. The use according to claim 5, characterized in that The multi-metal oxide, alkaline additive and 5-hydroxymethylfurfural solution are added to a microreactor with controllable temperature and pressure, and the microreactor is sealed to catalyze the oxidation of 5-hydroxymethylfurfural to generate 2,5-furandicarboxylic acid under the conditions of temperature of 100-150°C, oxygen pressure of 0.5-4 MPa and continuous magnetic stirring; after the reaction is completed, the multi-metal oxide material is centrifuged and recovered.

7. The use according to claim 6, characterized in that The concentration of the 5-hydroxymethylfurfural solution is 10-100 mM, and the mass ratio of the multi-metal oxide to 5-hydroxymethylfurfural is 1.2-2:1; the alkaline additive is sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or calcium hydroxide, and the molar ratio of the alkaline additive to 5-hydroxymethylfurfural is 1~4:1.

Citation Information

Patent Citations

  • Preparation method of copper-chromium-aluminum hydrotalcite catalyst and application of catalyst in catalytic oxidation of 5-hydroxymethylfurfural

    CN110586114A